Three-dimensional structure of entire hydrated murine hearts at histological resolution - Jasper Frohn; Frederik Böddeker; Marius Reichardt; Hendrik Bruns; Titus Czajka; Amara Khan; Ludovic Broche; Michael Krisch; Alberto Bravin; Frauke Alves; Jana Zschüntzsch; Tim Salditt (Scientific Reports)
Abstract Imaging the entire cardiomyocyte network in entire small animal hearts at single cell resolution is a formidable challenge. Optical microscopy provides sufficient contrast and resolution in 2d, however fails to deliver non-destructive 3d reconstructions with isotropic resolution. It requires several invasive preparation steps, which introduce structural artefacts, namely dehydration, physical slicing and staining, or for the case of light sheet microscopy also clearing of the tissue. Our goal is to provide 3d reconstructions of the cardiomyocyte network in entire hydrated murine hearts, and to develop a methodology for quantitative analysis of heart pathologies based on X-ray phase contrast computed tomography (XPCT). We have used XPCT at two beamlines of the extremely brilliant source (EBS) at the European Synchrotron Radiation Facility (ESRF) to scan wild-type murine hearts at high resolution, as well as a series of murine hearts of different pathological models, at reduced resolution and higher throughput. All hearts were obtained from the small animal facility of the university medical center in Göttingen. The hearts were fixed in formalin, stored and measured non-destructively in phosphate buffer solution. The high resolution dataset allows to discern individual cardiomyocytes in the tissue. All datasets have been analyzed using semi-automated image segmentation of the ventricles, rotation into a common coordinate system, classification into different anatomical compartments, and finally the structure tensor approach. A 3d streamline representation of the cardiomyocyte orientation vector field is provided. The different cardiovascular disease models are analysed based on metrics derived from the 3d structure tensor. An entire hydrated murine heart has been covered at an isotropic voxel size of 1.6 $$\upmu$$ μ m (distributed over several volumes). A binned and fused dataset of this heart is available at 3.2 $$\upmu$$ μ m, and has been analyzed by the structure tensor approach to yield the ventricular cardiomyocyte network or mesh, i.e. the aggregation of the cardiomyocyte chains in particular in the ventricular wall. Semi-automatic determination of structural metrics is already achieved and the corresponding tools and resulting data are made publically available. XPCT using extremely brilliant undulator radiation is close to achieve single cell reconstruction in an entire small animal organ.